2017
DOI: 10.1080/17518423.2017.1323970
|View full text |Cite
|
Sign up to set email alerts
|

Early development in Rett syndrome – the benefits and difficulties of a birth cohort approach

Abstract: Purposes: Typically, early (pre-diagnostic) development in individuals later diagnosed with Rett syndrome (RTT) has been investigated retrospectively using parent reports, medical records and analysis of home videos. In recent years, prospective research designs have been increasingly applied to the investigation of early development in individuals with late phenotypical onset disorders, for example, autism spectrum disorder. Methods: In this study, data collected by the Danish National Birth Cohort lent itsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Due to well-discussed limitations as well as benefits of both approaches (e.g., Marschik and Einspieler 2011; Ozonoff et al 2011; Palomo et al 2006), the prospective methods will unlikely fully replace the retrospective ones. Especially when studying rare diseases and disorders such as RTT, mainly caused by de novo mutations of the MECP2 gene, for which obtaining high-risk samples is unrealistic (Marschik et al 2018), retrospective procedures are still of great value.…”
Section: Discussionmentioning
confidence: 99%
“…Due to well-discussed limitations as well as benefits of both approaches (e.g., Marschik and Einspieler 2011; Ozonoff et al 2011; Palomo et al 2006), the prospective methods will unlikely fully replace the retrospective ones. Especially when studying rare diseases and disorders such as RTT, mainly caused by de novo mutations of the MECP2 gene, for which obtaining high-risk samples is unrealistic (Marschik et al 2018), retrospective procedures are still of great value.…”
Section: Discussionmentioning
confidence: 99%
“…For girls with Rett syndrome, early infant studies have revealed atypicalities before the age of two (Kerr & Stephenson, 1986;Bartl-Pokorny et al, 2013) and even in the first months of life (Einspieler et al, 2016), refuting a long-held belief that features of the disorder appear only after a period of typical early development. Findings such as these have decreased the mean age of diagnosis for classic Rett syndrome to around 2 ½ years old, although there is a need for additional study to acquire a comprehensive description of the syndrome's early development (Marschik et al, 2018).…”
Section: Early Detection Of Developmental Disordersmentioning
confidence: 99%
“…The variation in RTT presentation is associated with various factors, including: the nature of MECP2 mutation present [17][18][19][20], the degree of X-chromosome inactivation [21,22], the individual's genetic background; and the site and location of MeCP2 expression in the individual's brain [3]. Additional variability comes from the reports of demographic analysis from specific populations in several countries such as USA and Canada [23][24][25][26][27][28]; Italy [4,29]; Denmark [30][31][32]; Australia [5,[33][34][35][36][37][38][39]; UK [36,[40][41][42]; the Netherlands and Belgium [43,44]; Brazil [45]; Poland [46]; Sweden [47]; and an international analysis [48]. Due to this degree of variability in presentation, RTT is commonly misdiagnosed and often difficult to treat effectively, especially when considering differences in the genetic basis of the condition.…”
Section: Introductionmentioning
confidence: 99%